2009
DOI: 10.1016/j.foreco.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Population growth rate of a common understory herb decreases non-linearly across a gradient of deer herbivory

Abstract: (247 words).Overabundant white-tailed deer (Odocoileus virginianus) are a significant management problem in North America that exert unprecedented herbivory pressure on native understory forest communities. Conserving understory plant populations requires quantifying a sustainable level of deer herbivory. To date, most population projection models consider only deer presence and absence. To estimate population growth rate along a gradient of herbivory, we focused on Trillium grandiflorum because it is a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…Those studies mainly show that herbivory by deer and other large mammalian herbivores have strong negative effects on plant growth, reproduction, survival, and terrestrial carbon storage (Crête et al 2001, Russell et al 2001, Côté et al 2004, Knight et al 2009, MacDougall et al 2010. Herbivory on younger life cycle stage trees will eventually influence the structure of the future mature forest (Husheer et al 2006, Long et al 2007 Effects of deer on the growth of mature canopy trees have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those studies mainly show that herbivory by deer and other large mammalian herbivores have strong negative effects on plant growth, reproduction, survival, and terrestrial carbon storage (Crête et al 2001, Russell et al 2001, Côté et al 2004, Knight et al 2009, MacDougall et al 2010. Herbivory on younger life cycle stage trees will eventually influence the structure of the future mature forest (Husheer et al 2006, Long et al 2007 Effects of deer on the growth of mature canopy trees have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Belowground competition can be intense (Casper andJackson 1997, Bloor et al 2008) and has been demonstrated for both saplings and adult trees in other contexts (Bloor et al 2008, Montgomery et al 2010. Because understory vegetation represents an important fraction of forest biomass (Knight et al 2009, Heckel et al 2010 and is a substantial contributor to ecosystem transpiration (Yepez et al 2003), competition for water and nutrients may be important in structuring forest communities and could be strongly influenced by deer herbivory. Increased resource competition following reductions in deer population is suggested by a study involving muntjac deer (Muntiacus reevesi ) in a copice woodland in England where growth, survival, and recruitment of Corylus avellana and Crataegus laevigata all significantly decreased following a reduction in the deer population ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nonexperimental study, deer browse levels within a population were negatively correlated with population growth rate for another species in the genus, Trillium grandiflorum (51). Accordingly, Trillium represents a model for understanding the impact of deer on native species, and the loss of such browse-sensitive species can be a metric of decline in forest integrity (52). We predicted that, if ungulates disrupt the native community and enhance exotic invasion success, then in plots experimentally protected from deer: (i) native species would have higher reproductive success, (ii) Trillium fitness would increase and its density would increase, (iii) Alliaria fitness would decrease and its density would decline.…”
Section: Significancementioning
confidence: 99%
“…The negative effects of animals in the forest are fully demonstrated. For example, deers affect regeneration by foraging limiting its development, affecting the composition, structure and successional forest development (Green et al, 1997;Gill, & Beardall, 2001;O'Dowd et al, 2003;Rooney, & Waller, 2003;Knight, Caswell, & Kalisz, 2009;Takatsuki, & Ito, 2009;Koda, & Fujita, 2011;Shelton, Henning, Schultz, & Clay, 2014). Also, it has been demonstrated that a preference for palatability of certain plant species exists (Takatsuki, & Ito, 2009;Koda, & Fujita, 2011).…”
Section: Discussionmentioning
confidence: 99%